2006
DOI: 10.1783/147118906776276350
|View full text |Cite
|
Sign up to set email alerts
|

A novel device for removal of the retained intrauterine device

Abstract: Objective To evaluate the efficacy and acceptability of the Macaluso stent removal forceps for removal of retained intrauterine devices (IUDs) under direct vision using a hysteroscope in an outpatient setting.Methods Nineteen consecutive patients with a retained IUD who had been referred from primary care to the gynaecologists at the Conquest Hospital, Hastings, UK were included in the study. Attempts were made to remove the IUDs under direct vision using the Gynecare Versascope ® and Macaluso forceps. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…who reported success rates of 53% (95% CI 40–65) with Emmett and 59% (95% CI 47–70) with Retrievette ® retriever devices. However, our results were similar to the success rate of 94.7% (95% CI 84.6–100.0) reported with the use of outpatient hysteroscopy 9. Another recent study assessed the efficacy of ultrasound-guided use of a bent Cook catheter or a crochet-type hook when the threads were not retrievable using alligator forceps.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…who reported success rates of 53% (95% CI 40–65) with Emmett and 59% (95% CI 47–70) with Retrievette ® retriever devices. However, our results were similar to the success rate of 94.7% (95% CI 84.6–100.0) reported with the use of outpatient hysteroscopy 9. Another recent study assessed the efficacy of ultrasound-guided use of a bent Cook catheter or a crochet-type hook when the threads were not retrievable using alligator forceps.…”
Section: Discussionsupporting
confidence: 87%
“…In cases where these procedures fail, women are usually referred for IUD removal under direct vision using hysteroscopy. Although this is a very successful procedure, it has to be performed by highly skilled operators, it cannot be used in pregnant women and it is comparatively costly 6 9…”
Section: Introductionmentioning
confidence: 99%
“…There are several different IUS retrieval devices available, all of which have a similar success rates for removal. 3,5 There are several studies showing that inpatient and outpatient hysteroscopy is successful in most cases. However, blind manipulation does carry the risk of causing cervical or uterine injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Bounds et al 3 found that approximately 40% of IUSs with missing strings were removed with any device retriever and another 40% of IUSs were removed using the second choice of devices. 5 Safe administration of these anaesthetics requires that the woman be treated in a day-stay facility with all of its additional costs. 4 In cases where such devices have failed, cervical dilatation and or hysteroscopy are generally recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation